Bifunctional Squaramides as Organocatalysts for Lactide Polymerization: Catalytic Performance and Comparison with Monofunctional Analogues. Issue 15 (21st June 2017) - Specklin, David; Hild, Frédéric; Chen, Li; Thévenin, Lucas; Munch, Maxime; Dumas, Françoise; Le Bideau, Franck; Dagorne, Samuel
Abstract: Amine‐functionalized squaramides 1 and2 were prepared and shown to be suitable polymerization organocatalysts for the controlled ring‐opening polymerization (ROP) ofl ‐lactide (l ‐LA) in the presence of an alcohol source such as BnOH (which acts as an initiator) to afford chain‐length‐controlled and narrow‐dispersion poly(l ‐lactide) (PLLA) under mild reaction conditions. The ROP experimental and polymer analysis data are consistent with the action of1 and2 as bifunctional hydrogen‐bonding (HB) catalysts that are able to activate both the lactide monomer and initiator BnOH thanks to their dual HB acceptor and donor properties. As a comparison, aminosquaramide 3, a direct analogue of1 but a weaker HB donor because of the absence of electron‐withdrawing NH substituents, displays little lactide ROP activity, which highlights the key role of monomer activation through HB in the present systems. Unlike aminosquaramides 1 and2, related monofunctional squaramides 4 and5 are inactive inl ‐LA ROP in the presence of BnOH, but the addition of NEt3, as an external HB acceptor, allows the ROP to proceed with the production of well‐defined PLLA. A cooperative dual activation with an activated monomer/activated chain‐end mechanism is most likely operative in the lactide ROP mediated by1 and2 in the presence of BnOH. Abstract : One component or two : Single‐component aminosquaramides act as effective bifunctional hydrogen‐bonding catalysts for the controlled ring‐opening polymerization of lactide under mild conditions in the presence of BnOH. Such organocatalysts perform better in lactide ring‐opening polymerization than related squaramide/NEt3 two‐component catalysts.